A novel technique to design and production of coil spring in centre lathe. (2020) - Sathish, T.; Sabarirajan, N.; Chandramohan, D.; Karthick, S.
Abstract: In this investigation is mainly focused on to design and production of a coil spring in a center lathe machine. The lathe machine is simply operated by a simple electric power; it has different operating speeds to form a coil spring with using of tumbler gear mechanism. The tumbler gear mechanism used for to make different diameter of the spring with different pitch. In this research the different diameter of shaft held in the chuck to produce different diameter of spring. The main purpose of the shaft to act as a guide for producing a spring under the various dimensions. The wire guider unit is used to guide the raw material as a spring wire, the wire guider unit is fixed in the tool post and also it moves on the lathe bed freely by moving of carriage unit along on the bed. The lead screw rotation and automatic movement of carriage are achieved by the tumbler gear mechanism. Variety of size also can be produced easily with short period.